Graphic File Formats - Ricky Telg (EDIS)
When designing documents, you have to be aware of the different types of images you may receive. This 2-page fact sheet provides an overview of raster graphics and vector graphics. Written by Ricky Telg and published by the UF Department of Agricultural Education and Communication, June 2012.